Integrating Labs into Learning Environment - Jaanus, M.; Kukk, V.; Umbleja, K. (Elektronika ir Elektrotechnika, 2010)
In this paper, we present analysis of 2.5 year experience of integrating lab experiments into web-based learning environment. Previously, labs were provided in the classical format – experimental work with prescribed content that had to be replicated by a student (7 labs). From fall semester 2007, a new format was introduced where all practical work is based on the same model as theoretical tests: large number of simple experiments and a student has to obtain certain level of confidence. To reach that level minimum number of attempts is less than 10 but usually much more is needed. It was somewhat surprise how much this made passing the course more complicated for students. We present along with description of environment a detailed and critical analysis of learning process.